2020
DOI: 10.14260/jemds/2020/3
|View full text |Cite
|
Sign up to set email alerts
|

Smartphones- Help or Hindrance in Advancing Medical/Dental Education

Abstract: BACKGROUND Smartphone-a hand-held minicomputer housing in itself innumerable applications (Apps) from as simple as a clock to more complex apps like mobile banking etc. has completely revolutionized the very existence of human beings. There are myriads of apps available to the medical fraternity, which aids in not only practicing medicine but learning it too. The major advantage is the convenience it provides in accessing and organizing the data at a speed which is manually inconceivable. But as every coin has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…[26][27][28] Studies have reported that portability, time management, and easy access to data are some of the main reasons listed by the medical and dental students favoring increased usage of smartphones and mobile applications for e-learning. 26,29 With the presence of a multitude of research evidence supporting the use of smartphones and social media technology for educational purposes, many authors recommend designing programs, materials, and activities that are compatible with smartphone technology, thereby integrating this diverse learning approach as a part of the official teaching curriculum. 29,30 Results of our present survey showed an overall significant contrast between public and private dental school sectors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[26][27][28] Studies have reported that portability, time management, and easy access to data are some of the main reasons listed by the medical and dental students favoring increased usage of smartphones and mobile applications for e-learning. 26,29 With the presence of a multitude of research evidence supporting the use of smartphones and social media technology for educational purposes, many authors recommend designing programs, materials, and activities that are compatible with smartphone technology, thereby integrating this diverse learning approach as a part of the official teaching curriculum. 29,30 Results of our present survey showed an overall significant contrast between public and private dental school sectors.…”
Section: Discussionmentioning
confidence: 99%
“…26,29 With the presence of a multitude of research evidence supporting the use of smartphones and social media technology for educational purposes, many authors recommend designing programs, materials, and activities that are compatible with smartphone technology, thereby integrating this diverse learning approach as a part of the official teaching curriculum. 29,30 Results of our present survey showed an overall significant contrast between public and private dental school sectors. It was observed that public school students showed an overall higher dissatisfaction response rate to various features of virtual learning in comparison to private school students.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, it was shown that smartphone facilitated the teaching of anatomy via the use of visual aids, and it led to the enhancement of the learning experience [83]. The study conducted by Bansal et al revealed that smartphones have been widely used in the medical education system, but their use is still limited to sharing timetables, assignments, and staying connected with teachers and students [84]. The main advantages of smart devices are availability, portability, and easy access to the information 8…”
Section: International Journal Of Telemedicine and Applicationsmentioning
confidence: 99%